Experimental determination of surface heat transfer coefficient in a dry ice-ethanol cooling bath using a numerical approach - Santos, María V. (2017)
Fil: Santos, María V. Universidad Nacional de La Plata. Facultad de Ingeniería. Departamento de Ingeniería Química; Argentina